Diagnosing neglected pertussis in two pediatric case reports during the covid era: how is the prognosis - Astalitha Lorel Tania; Retno Nurhayati (Indonesian Pediatric Society, 2026)
Pertussis, caused by Bordetella pertussis, is a re-emerging and highly contagious respiratory infection that causes whooping cough in infants and older children. During the COVID-19 pandemic, diagnosis of pertussis has become more challenging because its respiratory manifestations often overlap with those of COVID-19. We report two cases of pertussis in children of different ages admitted to the pediatric ward of Aisyiyah Bojonegoro Hospital during the COVID-19 pandemic. The first case involved a 4-years-9 month-old boy who presented with persistent cough accompanied by a characteristic whooping sound for five days. The second case involved a 5-month-29-day-old girl who had experienced cough and low-grade fever for 21 days, marking her second episode of similar symptoms. Both patients were diagnosed with pertussis. These cases aim to describe and compare the clinical manifestations and outcomes of pertussis in children of different age groups. They also highlight the diagnostic challenges of pertussis during the COVID-19 pandemic in a region where pertussis remains a re-emerging disease. Pertussis in children may be underdiagnosed and underreported. Therefore, clinicians should consider pertussis in the differential diagnosis of children presenting with prolonged cough.